2009
DOI: 10.1002/fuce.200900029
|View full text |Cite
|
Sign up to set email alerts
|

Compression Properties and Leakage Tests of Mica‐Based Seals for SOFC Stacks

Abstract: Sealing properties and compression properties of two mica‐based materials, Thermiculite 866 and Statotherm HT were measured. Thermiculite 866 was tested in two forms: as‐made and precompressed (consolidated). Sealing tests were carried out at 800 °C with simulated fuel cell anode gas. Seals were pressed to a constant thickness, which represents the conditions in fuel cell stacks. Both seals showed stable leak rates over test periods of roughly 400 h. Leak rates of Thermiculite 866 samples were found to be inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…The same behaviour was found for Thermiculite® commercial gaskets (Rautanen et al, 2009) for which a 6 × 10 −2 atm·cm 3 ·s −1 ·m −1 leak rate was reported in the temperature range of 25-600°C at 5 bar He, under 20 MPa. Using the same unity, for our gaskets (circumference 40.8 mm) the leak rate value equal to 2.5 × 10 −2 atm·cm 3 ·s −1 ·m −1 is comparable to the one of Thermiculite® commercial gaskets.…”
Section: Sealing Properties At High Temperaturessupporting
confidence: 75%
See 2 more Smart Citations
“…The same behaviour was found for Thermiculite® commercial gaskets (Rautanen et al, 2009) for which a 6 × 10 −2 atm·cm 3 ·s −1 ·m −1 leak rate was reported in the temperature range of 25-600°C at 5 bar He, under 20 MPa. Using the same unity, for our gaskets (circumference 40.8 mm) the leak rate value equal to 2.5 × 10 −2 atm·cm 3 ·s −1 ·m −1 is comparable to the one of Thermiculite® commercial gaskets.…”
Section: Sealing Properties At High Temperaturessupporting
confidence: 75%
“…They contain few talc particles and can resist up to 800°C (Hoyes, 2007). Upon 100 mbar of hydrogen and a compressive stress of 4-8 MPa, the leak rate was found to be close to 1-3 · 10 − 1 atm·cm 3 ·s − 1 (Rautanen et al, 2009). Upon 15 mbar of a mixture of N 2 -H 2 (50/50 vol.)…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Compressible seals would have required much larger compression stress to flatten the cutting burrs. Additionally, the gap clearance variation would have likely been an issue due to the limited compressibility of Thermiculite 866 [5]. There are many reasons that can lead to a variation of gap clearance in a stack, i.e.…”
Section: Glass Compliancementioning
confidence: 97%
“…Compressible seals composed of mica-type paper have been investigated as an alternative [5e7]. The drawback of compressive seals is that in order to achieve acceptable leak rate, a compression stress of the order of several MPa has to be applied on the stack [5]. However, it was found that the leak rate remains significantly higher compared to glass ceramic seals and that the needed level of compression and the necessary compression system becomes technically challenging for large footprint stack.…”
Section: Introductionmentioning
confidence: 99%